2018
DOI: 10.1001/jama.2018.17242
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oral Anticoagulants and Proton Pump Inhibitor Cotherapy With Hospitalization for Upper Gastrointestinal Tract Bleeding

Abstract: Importance: Anticoagulant choice and proton pump inhibitor (PPI) co-therapy could affect risk of upper gastrointestinal bleeding, a frequent and potentially serious complication of oral anticoagulant treatment. Objective: Compare upper gastrointestinal bleeding hospitalization incidence for individual anticoagulants without and with PPI co-therapy and determine variation according to underlying gastrointestinal bleeding risk. Design, Setting, and Participants: Retrospective cohort study in Medicare patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
142
2
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(174 citation statements)
references
References 30 publications
9
142
2
11
Order By: Relevance
“…3 The increase in upper GIT bleeding risk with rivaroxaban and dabigatran compared with apixaban was also recently demonstrated in a large population based study of US Medicare beneficiaries. 14 The topical anticoagulant effect of NOACs is proposed to be the mechanism of increased GIT bleeding risk compared with warfarin. The direct thrombin inhibitor dabigatran is associated with lower GIT bleeding, a finding attributed to incomplete absorption and increasing concentrations in the lower GIT tract, in addition to the direct caustic effect of its tartaric acid content on the upper GIT mucosa.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…3 The increase in upper GIT bleeding risk with rivaroxaban and dabigatran compared with apixaban was also recently demonstrated in a large population based study of US Medicare beneficiaries. 14 The topical anticoagulant effect of NOACs is proposed to be the mechanism of increased GIT bleeding risk compared with warfarin. The direct thrombin inhibitor dabigatran is associated with lower GIT bleeding, a finding attributed to incomplete absorption and increasing concentrations in the lower GIT tract, in addition to the direct caustic effect of its tartaric acid content on the upper GIT mucosa.…”
Section: Discussionmentioning
confidence: 90%
“…Conversely, apixaban had similar GIT bleeding risk to warfarin . The increase in upper GIT bleeding risk with rivaroxaban and dabigatran compared with apixaban was also recently demonstrated in a large population based study of US Medicare beneficiaries . The topical anticoagulant effect of NOACs is proposed to be the mechanism of increased GIT bleeding risk compared with warfarin.…”
Section: Discussionmentioning
confidence: 95%
“…Warfarin control is affected by numerous factors including drug interactions . PPIs have been reported to interact with warfarin resulting in increased INR and bleed risk, however the clinical significance of this interaction remains unclear because of conflicting reports particularly regarding bleeds . This study aimed to determine the impact on warfarin control with concurrent administration of PPIs as measured by warfarin TTR and bleed events.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Henriksen et al reported no evidence that PPIs affected INR values in the few weeks after PPI initiation, whilst Shirayama et al reported no change in warfarin dose or INR for more than 6 weeks after addition of PPIs. In terms of bleeds, Nagata et al reported no increased risk of bleeding with PPIs, whilst two studies by Ray et al reported a reduced risk of gastrointestinal bleeds in patients taking PPIs with warfarin. Thus, there remain conflicting data in regard to the interaction with warfarin and PPIs when bleeds and/or INR are reported as endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…В сравнении с пациентами без мультиморбидности больные в группе с высоким ее уровнем были старше (средний возраст, соответственно, 69 и 74 лет), принимали в два раза большее количество препаратов (5 против 10) и имели больший балл по шкале CHA 2 DS 2 -VASc (2,7 против 4,9) (р<0,001 во всех случаях). Скорректированная распространенность на 100 пациенто-лет сочетания инсульта/системных тром-боэмболических осложнений, смертности и массивных кровотечений возрастала по мере увеличения мультиморбидности (группа без мультиморбидности рассматривалась в качестве референсной; ОР в группе умеренной мультимопбидности = 1, 42 [19,20]. Его первичной целью явился сравнительный анализ по критерию «не хуже» терапии апиксабаном и антагонистом витамина К (целевой уровень МНО 2,0-3,0) в отношении составной конечной точки из массивных и клинически незначимых кровотечений у больных с ФП в сочетании с острым коронарным синдромом и/или с наличием необходимости проведения чрескожного коронарного вмешательства, которым планировалось назначение ингибиторов P2Y 12 рецепторов тромбоцитов по меньшей мере на 6 мес.…”
Section: Introductionunclassified